Infants‎ breastfed‏: a require or a potential risk - Taghizadeh, Mansoreh; Afshar, Parvaneh; Madani, Golnoush; Mohammad Hasani, Fatemeh; Khoshhali, Mehri; Zamanfar, Daniel; Rouhanizadeh, Hamed; Vahedi Larijani, Lale (Progress in Nutrition, 2018)
The Ochratoxin A(OTA) is a nephrotoxic and carcinogenic mycotoxin which generates important risks for human health worldwide owing to food contamination merchandise, environment. Dietary contaminants ingested by nursing mothers can be found in their breast milk. Nevertheless, the rate of OTA lactation transfer has not been investigated so far at various stages of breastfeeding. The study aimed at assessing the presence and values of the mycotoxin Ochratoxin A in human milk in Isfahan, Iran, and sought to evaluate the potential risk for the newborn babies based on the mycotoxin taking. 41 lactating women were randomly selected and breast milk samples after delivery were taken to determine the prevalence of Ochratoxin A value by enzyme linked immunosorbent assay and high performance liquid chromatography technique. Considering the total samples analyzed, only one case was contaminated with Ochratoxin A at 45 ng/l. Accordingly, the results indicated the exposure of mothers and neonates to Ochratoxin A and although the observed incidence was low, it is recommended that further investigations be conducted on mycotoxin contamination in large quantity both in food and biological fluids in addition to protection strategies to decrease the risk in Isfahan and other parts of the country.